Molecular Mechanism of N,N-Dimethylformamide Degradation in Methylobacterium sp. Strain DM1 - Lu, Xinyu (Appl Environ Microbiol, 2019)
N,N-Dimethylformamide (DMF) is one of the most common xenobiotic chemicals, and it can be easily emitted into the environment, where it causes harm to human beings. Herein, an efficient DMF-degrading strain, DM1, was isolated and identified as Methylobacterium sp. This strain can use DMF as the sole source of carbon and nitrogen. Whole-genome sequencing of strain DM1 revealed that it has a 5.66-Mbp chromosome and a 200-kbp megaplasmid. The plasmid pLVM1 specifically harbors the genes essential for the initial steps of DMF degradation, and the chromosome carries the genes facilitating subsequent methylotrophic metabolism. Through analysis of the transcriptome sequencing data, the complete mineralization pathway and redundant gene clusters of DMF degradation were elucidated. The dimethylformamidase (DMFase) gene was heterologously expressed, and DMFase was purified and characterized. Plasmid pLVM1 is catabolically crucial for DMF utilization, as evidenced by the phenotype identification of the plasmid-free strain. This study systematically elucidates the molecular mechanisms of DMF degradation by Methylobacterium. IMPORTANCE DMF is a hazardous pollutant that has been used in the chemical industry, pharmaceutical manufacturing, and agriculture. Biodegradation as a method for removing DMF has received increasing attention. Here, we identified an efficient DMF degrader, Methylobacterium sp. strain DM1, and characterized the complete DMF mineralization pathway and enzymatic properties of DMFase in this strain. This study provides insights into the molecular mechanisms and evolutionary advantage of DMF degradation facilitated by plasmid pLVM1 and redundant genes in strain DM1, suggesting the emergence of new ecotypes of Methylobacterium.